Caliste-MM: a spectro-polarimeter based on the micromegas concept for soft X-ray astrophysics. (12th April 2016) - Serrano, P.; Attié, D.; Desforge, D.; Ribas, E. Ferrer; Jeanneau, F.; Limousin, O.
Abstract: Performing X-ray polarimetry of astrophysical sources is a topic of growing interest, with only a few flying experiments dedicated to it so far. For soft X-rays sources detection from 1 keV to a few tens of keV, the best technique certainly consists in using the photoelectric effect, which is the dominant phenomenon at those energies in gaseous detectors. One of the main issues is the gaseous detector's reliability in space and the sensitivity to sparks of their associated front-end electronics caused by cosmic rays. To overcome this limitation, we investigate the opportunity of building a new spectro-polarimeter with outer and contactless radiation hard readout electronics, placed outside the gas chamber. In order to perform this, we use a Micromegas detector with a resistive anode spread on a ceramic plate. The signal is then transmitted by capacitive coupling to the outer electronics. The readout electronics in question, inherited from Caliste-HD, consists of a fine pitch 3D detector module developed at CEA initially designed for semi-conductor applications. In this paper we present the different parts of our experimental setup as well as recent results obtained by illuminating our prototype with an 55 Fe source. In addition to the optimization of the detector's parameters, we also present the first spectrum of a soft X-ray gaseous detector with outer and contactless electronics and photo-electron tracks obtained with the detector making a step forward in the field of soft X-rays spectro-polarimeter.